Gut Microbiological Disorders Reduce Semen Utilization Rate in Duroc Boars - Guo, Liangliang; Wu, Yinghui; Wang, Chao; Wei, Hongkui; Tan, Jiajian; Sun, Haiqing; Jiang, Siwen; Peng, Jian (Frontiers in Microbiology, 2020)
Although rising evidence suggests that the gut microbiota is closely related to host health, the effects of gut microbiota on male fertility are still rarely explored. This study was to investigate the gut microbiota composition and function, fecal short-chain fatty acids, intestinal permeability, and systemic inflammatory status of Duroc boar with high (H group, 100%) and low (L group, <80%) semen utilization rate. Fecal samples, analyzed by 16S ribosomal RNA gene sequencing, displayed taxonomic and functional changes between boars with high and low semen utilization rates. For the gut microbiota composition of the boars, four genera were different between the two groups. The [Ruminococcus] and Sphingobium were enriched in L group boars then negatively correlated with the semen utilization rate. While RFN20 and Paludibacter were enhanced in the H group, only RFN20 showed significantly positively correlated with the semen utilization rate of boars. In addition, changes in the metabolic function of the gut microbiota of the two groups were found, including altered branched-chain fatty acids production. Significant increases in plasma endotoxin, zonulin, and diamine oxidase, lipocalin-2 levels were observed in boars with low semen utilization, and also a similar trend of IL-6, TNF-α was found. However, the concentration of IL-10 in plasma of boars with high semen utilization rate showed an increasing tendency. These results indicated increased intestinal permeability and systemic inflammation in boars with low semen utilization. Data showed that the composition and functions of gut microbiota varied between boars with high or low semen utilization rates while the semen utilization rate is notably correlated with the gut microbiota composition, intestinal permeability, and inflammatory status of the boar.